Thermal properties, thermo-oxidation and UV-thermo-humidity complex stability of polyethylene/modified fly ash/ultraflow composites - Chinh, Nguyen Thuy; Thu Trang, Nguyen Thi; Mai, Tran Thi; Giang, Nguyen Vu; Trung, Tran Huu; Huynh, Mai Duc; Hoang, Thai (Vietnam Journal of Chemistry, 2017)
This study concerns the effect of ultraflow (UTF) content on the thermal property; thermo-oxidation and photo thermal-humidity stability of composites based on high density polyethylene (HDPE) and modified fly ash (MFA). The different scanning calorimeter analysis (DSC) results show that the relative crystallinity of HDPE/MFA and HDPE/MFA/UTF composites is lower than that of HDPE. The thermal properties of HDPE/MFA/UTF composites were studied by using thermogravimetric analysis (TGA) characteristic. Thermal stability of HDPE/MFA/UTF composites is higher than HDPE and HDPE/MFA composite. The tensile properties (tensile strength, elongation at break and Young’s modulus) of the composites after thermal aging test had a tendency to reduce with increasing the UTF contents. The retention of tensile strength and Young’s modulus of HDPE/MFA/UTF composites is larger than that of HDPE/MFA composite while the elongation at break of HDPE/MFA/UTF composites  is less than that of HDPE/MFA composite. The results of accelerated weathering test showed that the tensile strength, elongation at break and Young’s modulus of HDPE/MFA/UTF composites after 168 hour accelerated weathering test were increased much higher than those of HDPE/MFA composites. Keywords. Ultraflow, thermal property, thermal oxidation, accelerated weathering test, HDPE composite.